Exploring factors determining students’ online homework adoption with an extended UTAUT2 model - Chen, Liu; Shen, Yanan; Wong, Su Luan (Routledge, 2026)
Online homework (OHW) holds significant potential for student learning. However, there is a tendency among secondary students in China to exhibit a low inclination to adopt this facilitator. Drawing on an extension of the Unified Theory of Acceptance and Use of Technology (UTAUT2) model, this study explored the factors determining Chinese secondary students’ intention to utilize an OHW system for learning via convenience sampling and a quantitative design. Data were collected from 97 out of 421 students via questionnaires in a voluntary context. Through the Partial Least Square-Structural Equation Modeling (PLS-SEM) approach, this study found that students’ intention to embrace OHW was influenced by technological self-efficacy, attitude, and social influence. Besides, technological self-efficacy and hedonic motivation also affected students’ attitude toward the system. The findings underscore the importance of boosting students’ confidence in using technology, exerting positive social influence, and incorporating engaging assignments to enhance students’ adoption of OHW technology.